2014
DOI: 10.1163/15707563-00002431
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of sexual size dimorphism supports the inverse of Rensch’s rule in two frog species

Abstract: Rensch’s rule describes that sexual size dimorphism (SSD) increases with body size (hyperallometry) when males are larger, and decreases with body size (hypoallometry) when males are smaller. In this paper, on the basis of mean adult body size resulting from 18 populations of the common frog Rana temporaria and 24 populations of the Tibetan frog Nanorana parkeri, we tested the consistency of allometric relationships between males and females with Rensch’s rule. Our results show that the variation in degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In S. fuscovarius, body size in both sexes increases with longitude but female size exhibited a steeper longitudinal cline which is opposite to Rensch's rule but consistent with other anuran species (Liao & Chen 2012;Liao 2013;Lu et al 2014;Liao et al 2015). Therefore, it seems that in anurans the inverse of Rensch's rule is a constant or at least for species with a femalesbiased dimorphism.…”
Section: Sexual Size Dimorphismsupporting
confidence: 72%
See 1 more Smart Citation
“…In S. fuscovarius, body size in both sexes increases with longitude but female size exhibited a steeper longitudinal cline which is opposite to Rensch's rule but consistent with other anuran species (Liao & Chen 2012;Liao 2013;Lu et al 2014;Liao et al 2015). Therefore, it seems that in anurans the inverse of Rensch's rule is a constant or at least for species with a femalesbiased dimorphism.…”
Section: Sexual Size Dimorphismsupporting
confidence: 72%
“…This means that the variation in SSD results from females being more sensitive to climatic factors. In other anuran species with females-biased dimorphism, intraspecific variation in SSD was only related to latitude, increasing to the south like in Limnodynastes tasmaniensis (Sch€ auble 2004), temperature as in Bufo andrewsi (Liao 2009), or without any correlation at all with geographic and climatic variables like in B. bufo, Nanorana parkeri, Rana temporaria and R. kukunoris (Sch€ auble 2004;Cvetkovic et al 2008;Lu et al 2014;Feng et al 2015). Differently, in species with male-biased dimorphism SSD appears related to precipitation but with contrasting results; SSD was greater where precipitation is higher such as in L. peronii (Sch€ auble 2004) or lower as in Paa spinosa (Yu et al 2010).…”
Section: Sexual Size Dimorphismmentioning
confidence: 99%
“…The regression of SSD on body size (Figure 1) of the data for SSD and body size (Table 1) indicates a positive regression to reject Rensch's rule in Centrobolus. Although the null hypothesis is accepted and the rule rejected the inverse relationship is true [26][27][28][29][30][31][32] . This was seen in the SSD increases with body size.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, interspecific studies of amphibians have revealed that SSD in amphibians does not follow Rensch's rule, but rather its inverse (Han and Fu 2013;De Lisle and Rowe 2013;Liao et al 2013). However, intraspecific tests of Rensch's rule in amphibians are, as yet, rare (but see Liao and Chen 2012;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 99%